2018
DOI: 10.1002/mnfr.201800612
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 Deficiency Promotes High‐Fat Diet‐Induced Nonalcoholic Fatty Liver Disease in Correlation with Impaired Intestinal Permeability through Gut Microbial Dysbiosis

Abstract: Scope Sirtuin 3 (SIRT3) plays a protective role against nonalcoholic fatty liver disease (NAFLD) by improving hepatic mitochondrial dysfunction. Gut microbiota imbalance contributes to the pathogenesis of NAFLD, yet the underlying mechanism linking SIRT3 with gut microbiota in NAFLD progression remains obscure. Methods and results Wild‐type 129 mice and SIRT3 knockout (SIRT3KO) mice are placed under a chow diet or high‐fat diet (HFD) treatment for 18 weeks. HFD resulted in a significantly increased hepatic ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 51 publications
3
51
1
Order By: Relevance
“…The elevated relative abundance of Oscillibacter spp. correlated with the severity of NAFLD (41). In our study, pretreatment with B. longum R0175 significantly reduced the enrichment of Butyricimonas spp., B. virosa, and Oscillibacter spp., indicating that the shifts in the relative abundances of these microbes may be implicated in the protective effects of the probiotic against acute liver failure in rats.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The elevated relative abundance of Oscillibacter spp. correlated with the severity of NAFLD (41). In our study, pretreatment with B. longum R0175 significantly reduced the enrichment of Butyricimonas spp., B. virosa, and Oscillibacter spp., indicating that the shifts in the relative abundances of these microbes may be implicated in the protective effects of the probiotic against acute liver failure in rats.…”
Section: Discussionsupporting
confidence: 61%
“…and intestinal mucosal injury scores, which was consistent with previous studies showing that the enrichment of Oscillibacter spp. positively correlated with intestinal mucosal barrier impairment (40,41). We found that the R0175 group harbored an increased relative abundance of bacteria of the genus Alloprevotella, which can indirectly produce short-chain fatty acids (SCFAs).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Chen et al. suggested the crucial role of Oscillibacter in high fat diet‐induced intestinal dysfunction, but also the positive association with digestive diseases and more severe DSS‐induced colitis . In our study, the relative abundance of Oscillibacter was increased by DSS administration and was attenuated by TEs treatment, which is consistent with Peng et al.…”
Section: Resultsmentioning
confidence: 98%
“…Significant attenuation of DSS‐induced increase in Oscillibacter were observed in all TE‐treated groups. The positive and negative effects of Oscillibacter were reported in various literature . Arpaia et al.…”
Section: Resultsmentioning
confidence: 99%
“…The animal diet was provided as previously described . Briefly, chow diet (10% fat, 70% carbohydrate, 20% protein; D12450H) was obtained from Research Diets.…”
Section: Methodsmentioning
confidence: 99%